Reflections on War Preparedness and Consequences - Liebenberg, Ian (African Sun Media, 2012)
Reflections on War is a comprehensive and objective investigation into the problems of war. The book explores the crucial link between theory, strategy and objectives in war, taking all the evidence and theory into account, and should be of interest to military practitioners, specialists in defence studies, and others interested in military history. Also notable about the work is its ability to draw insights together from international legal theory, management sciences, history, sociology and the political economy of war - showing due respect for the moral complexities involved in waging war.